The Impact of High Indicators of Deposits and Loans on Banking Liquidity an Applied Study in Some Banks Registered in the Iraq Stock Exchange - Hayder Abbas AL-Attar; Sarah Abdulameer K; Dhurgham Mezher Oleiwi (HM Journals, 2023)
From the theoretical side, the study aims to demonstrate the impact of the theoretical relationship between the variables of the independent study, bank deposits and loans, with the dependent variable on bank liquidity. National Bank of Iraq, the Iraqi Middle East Investment Bank, and the Gulf Commercial Bank). And then find the statistical correlation and the effect of the high percentage of bank deposits and bank loans on bank liquidity by using the statistical analysis program (SPSSv.26) to reach the most important results that proved the existence of a correlation between bank deposits and bank liquidity for the value of the correlation (0.804**) at Significance level (0.01). As well as the existence of a correlation between bank loans and bank liquidity on the value of the correlation (0.301 *) at a significant level (0.01). The existence of a relationship of effects that occur in the dependent variable banking liquidity as a result of the influence of the independent variable bank deposits, as the coefficient of determination (R ^ 2) reached a value of (0.647) and the existence of a relationship of effects that occur in the dependent variable bank liquidity as a result of the influence of the independent variable bank loans as it reached The coefficient of determination (R^2) is (0.091).